The 2008 federal intervention to stabilize Fannie Mae and Freddie Mac - W. Scott Frame (Federal Reserve Bank of Atlanta, 2009)
Fannie Mae and Freddie Mac are government-sponsored enterprises that play a central role in U.S. residential mortgage markets. In recent years, policymakers became increasingly concerned about the size and risk-taking incentives of these two institutions. In September 2008, the federal government intervened to stabilize Fannie Mae and Freddie Mac in an effort to ensure the reliability of residential mortgage finance in the wake of the subprime mortgage crisis. This paper describes the sources of financial distress at Fannie Mae and Freddie Mac, outlines the measures taken by the federal government, and presents some evidence about the effectiveness of these actions. Looking ahead, policymakers will need to consider the future of Fannie Mae and Freddie Mac as well as the appropriate scope of public sector activities in primary and secondary mortgage markets.
Keywords: G21; G28; 330; government-sponsored enterprises; mortgages; securitization; conservatorship